Dogmatyka prawa wobec politycznej opresji : czy historia myśli prawnej może nas czegoś nauczyć? - Bator, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
One of the contemporary views formulated and popularized mainly by authors from the so-called critical theory of law is the belief in the inevitable, mutual relationship of law (theory of law and dogmatics of law) and legal practice (adjudication) with politics and the political. This position is strengthened by the observation of contemporary disputes — especially visible in Poland — with the participation of politicians and lawyers: politicians accuse lawyers of political motivation of actions taken to defend the judiciary and the rule of law, while lawyers defend themselves by arguing the need for autonomy of their professional practice, including its apolitical nature. In this text, I explain the arguments of the latter party to the dispute. I choose the dogmatics of law as the field of illustrating the issues raised, since it occupies a special place in the continental legal scholarship, acting as an intermediary between the jurisprudence and legal decision-making practice. I am trying to show — by referring to two examples from general history, i.e. the eleventh-century investiture controversy and the nineteenth-century debate in the background of the German reunification idea — that law and politics (lawyers and politicians) have always been forced to compete and cooperate with each other. Thus, it confirms the thesis of the critical theory of law. At the same time, however, I try to show that the legal community had the ability to “learn” from the political disputes of the past, which led to the formation of independent jurisprudence and legal practice in the face of current politics, and thus also to apoliticality. What is more, I argue that such an apolitical nature is a condition for the survival of legal culture in its present shape — and here, my path diverges from the critical legal theory claims. However, in my opinion, the contemporary arguments made within this theory about the political science of law and jurisprudence should be treated with all seriousness — as another experience from which our community, as one can hope, will be able to draw informative conclusions.
Keywords: europejska kultura prawna; paradygmat dogmatyki prawa; polityczność prawa; rewolucja w prawie; niemiecka szkoła historyczna